Pengembangan Modul Pembelajaran Berbasis Proyek (PjBL) pada Mata kuliah Motor Diesel untuk Meningkatkan Kompetensi Kognitif dan Psikomotor Mahasiswa - Sugiarto, Toto; Jalinus, Nizwardi; Ridwan, Ridwan; Putra, Dwi Sudarno; Wagino, Wagino (Universitas Negeri Padang, 2023)
Learning requires supporting materials in the form of reliable teaching materials, one of which can be a learning module. Therefore, it is necessary to add project-based learning modules in diesel motor courses to develop existing modules. This study aimed to measure the validity, practicality, and effectiveness of developing project-based diesel motor course learning modules. This research is included in the type of research and development (R&D). The model used in this study uses the ADDIE principle, data collection methods through questionnaires and learning outcomes tests, data analysis is processed using a quantitative approach from the application of the module and described through a qualitative approach to conclude the results of the study, the research subject consists of lecturers and students majoring in automotive engineering. The results of the research on the development of PjBl-based modules meet the feasibility of validity, practicality, and effectiveness. In its implementation, the results of the analysis of the validity aspect of the module development from the validator are 88.07% with very valid criteria, and the practicality aspect of the module development scores 86.92% with very practical criteria. The effectiveness aspect of module development is seen from the knowledge and project tests. The results of the knowledge test on 30 students and get a good average score value, amounting to 85.66%, and the field of skills or projects of 85.66%, thus achieving very high criteria.